Attribution of the topographical descriptions of Kharkov province of the last quarter of XVIII century - Pirko, Vasyl; Petrova, Inna (Skhid, 2013)
The article is devoted to the origin problems of the topographical descriptions ofKharkovprovince of the last quarter of XVIII century and the definition of their origin bases. The historical circumstances that have been led to appearance of this groups of documents were defined by the author, the basic customer documents of realization the topographical descriptions, a number of authors of the topographical descriptions ofKharkovprovince were defined.